1991
DOI: 10.1056/nejm199103143241105
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Relation between Blood Pressure and Insulin Resistance

Abstract: The relations between insulinemia, insulin resistance, and blood pressure differ among racial groups and may be mediated by mechanisms active in whites, but not in Pima Indians or blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
6
6

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(210 citation statements)
references
References 37 publications
11
183
6
6
Order By: Relevance
“…An association between hyperinsulinaemia and hypertension has also been reported in several studies (7-11). Increased peripheral insulin resistance, independent of the degree of obesity, has also been found in hypertensive subjects using euglycemic insulin clamp technique (12)(13)(14).…”
mentioning
confidence: 99%
“…An association between hyperinsulinaemia and hypertension has also been reported in several studies (7-11). Increased peripheral insulin resistance, independent of the degree of obesity, has also been found in hypertensive subjects using euglycemic insulin clamp technique (12)(13)(14).…”
mentioning
confidence: 99%
“…22 The role of HT as a factor influencing CHD risk in subjects with MS is under debate, particularly in the elderly. 23 Saad et al 24 stated that the higher prevalence of HT observed in European than in African/Asian people is one of the possible reasons influencing higher CHD mortality observed in subjects with MS. Shen et al 25 suggested that HT is related to MS only secondary to other mechanisms activated by insulin resistance and hyperinsulinemia, that is increased renal sodium and water retention, plasma noradrenaline and sympathetic nervous system activity. [26][27][28] Grundy et al 29 believe that HT is 'less metabolic' than other metabolic- Another potential confounder about the role of HT in MS is aging, because both HT and MS increase in prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, no correlation between high blood pressure (BP) and hyperinsulinemia was found in obese subjects by Grugni et al (9). Saad et al showed the racial differences in the relation between BP and insulin resistance (10). Despite the obvious importance and clinical magnitude of the problem, the nature of the relationship between obesity and hypertension has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Euglycemic insulin clamp procedure Since this method has been previously described in detail (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14], only the general procedure will be outlined here.…”
Section: Blood Pressurementioning
confidence: 99%